2020
DOI: 10.1080/03007995.2020.1840970
|View full text |Cite
|
Sign up to set email alerts
|

Phases of fluid management and the roles of human albumin solution in perioperative and critically ill patients

Abstract: Objective: Positive fluid balance is common among critically ill patients and leads to worse outcomes, particularly in sepsis, acute respiratory distress syndrome, and acute kidney injury. Restrictive fluid infusion and active removal of accumulated fluid are being studied as approaches to prevent and treat fluid overload. Use of human albumin solutions has been investigated in different phases of restrictive fluid resuscitation, and this narrative literature review was undertaken to evaluate hypoalbuminemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 154 publications
(187 reference statements)
2
22
0
3
Order By: Relevance
“…We congratulate the author for producing a comprehensive review on the physiology of albumin and its role in perioperative and critically ill patients. However, we disagree with the statement "Albumin has a variety of biological properties and functions, including … buffering capabilities, which may be especially relevant in critically ill patients" [1].…”
Section: Accepted Manuscriptmentioning
confidence: 68%
See 1 more Smart Citation
“…We congratulate the author for producing a comprehensive review on the physiology of albumin and its role in perioperative and critically ill patients. However, we disagree with the statement "Albumin has a variety of biological properties and functions, including … buffering capabilities, which may be especially relevant in critically ill patients" [1].…”
Section: Accepted Manuscriptmentioning
confidence: 68%
“…We read with interest the recent review in this Journal by Christian Wiedermann [1]. We congratulate the author for producing a comprehensive review on the physiology of albumin and its role in perioperative and critically ill patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Diuretics are frequently prescribed in the critically ill to facilitate liquid removal and have become a pharmacologic adjuvant therapy in ARDS [20] . Studies found that compared with liberal uid strategy or standard care, conservative uid management achieved by restricting uid intake, use of diuretics or hemo ltration, was associated with improved oxygenation, increased ventilation free days, and decreased mortality [21][22][23][24] . What's more, it has been proposed that correction of uid retention may rely on diuretics or renal replacement therapy once the hemodynamic status is stabilized [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Die "International Fluid Academy" (IFA) empfiehlt HA 20 % bei schweren Verbrennungen, vor allem in der sog. Deresuscitation-Phase [63], also nach initialer Stabilisierung, um dem "fluid creep" entgegen zu wirken [37].…”
Section: Albumin Bei Verbrennungenunclassified